(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article examines the pivotal role of innovative teaching methods in modern education. It argues that traditional approaches are increasingly being complemented by interactive, student-centered methods that enhance engagement, foster critical thinking, and equip learners with 21st-century skills. The article explores various innovative techniques, including gamification, project-based learning, flipped classrooms, virtual reality, and blended learning, highlighting their benefits and challenges. It concludes that embracing innovative approaches is crucial for unlocking student potential, fostering a love for learning, and preparing learners for a future that demands adaptability, creativity, and critical thinking, innovative teaching methods", "educational technology", "technology